Beveridge, Bevan and institutional change in the UK welfare state. (18th August 2021) - Greener, Ian; Powell, Martin
Abstract: This paper explores the changes to social security and health proposed in the Beveridge Report through the lens of the framework proposed by Mahoney and Thelen for exploring the relationship between political and institutional contexts, change‐agents and types of institutional change. We find that, in terms of social security, the Beveridge Report led to 'layering' in that it both built on an inherited legacy of institutions from the earlier Liberal Reforms. Although Beveridge assumed the existing of a national health service for his social security plans to work, he did not specify what form such a service could take. Bevan had the advantage of being a Minister of Health with a large government majority, but had to deal with both internal (in Cabinet) and external (primarily from the medical profession) attempts to veto his reforms. Bevan's changes to healthcare have to be seen in that context, as well as in relation to his own pragmatism, in converting the wartime Emergency Medical Service into the National Health Service. By utilising the full Mahoney and Thelen framework in two cases that were near contemporary with one another, but when contrasted with one another, we show the potential of the framework in cross‐case analysis in illuminating the relationship between political and institutional context, change‐agents, the type of change that results.